I need to calculate the sum $\displaystyle S=\sum_{n=1}^\infty\frac{(-1)^n}n H_n^2$, where $\displaystyle H_n=\sum\limits_{m=1}^n\frac1m$.

Using a CAS I found that $S=\lim\limits_{k\to\infty}s_k$ where $s_k$ satisfies the recurrence relation \begin{align} & s_{1}=-1,\hspace{5mm} s_{2}=\frac18,\hspace{5mm} s_{3}=-\frac{215}{216},\hspace{5mm} s_{4}=\frac{155}{1728},\hspace{5mm} \text{for all} \quad k>4, \\ s_{k} &=\frac1{k^3(2k-3)}\left(\left(-4k^4+18k^3-25k^2+12k-2\right)s_{k-1}+\left(12k^3-39k^2+38k-10\right)s_{k-2} \right.\\ & \hspace{5mm} \left. +\left(4k^4-18k^3+25k^2-10k\right)s_{k-3}\\+\left(2k^4-15k^3+39k^2-40k+12\right)s_{k-4}\right), \end{align} but it could not express $S$ or $s_k$ in a closed form.

Can you suggest any ideas how to calculate $S$?

  • $\begingroup$ Is that just $(H_n)^2$ or $H_n^{(2)}$? $\endgroup$ – Ali May 29 '13 at 4:22
  • 1
    $\begingroup$ Looking at the definition of $H_n$, lack of $\,{}^{(\phantom2)}$ around ${}^2$ and the values of partial sums, I would assume $(H_n)^2$. $\endgroup$ – Vladimir Reshetnikov May 29 '13 at 4:38
  • $\begingroup$ The $s$ sequences make a real vector space of dimension 4. So, if you manage to find the sequences with $(s_1, s_2,s_3,s_4) = (1,0,0,0), $ then $(s_1, s_2,s_3,s_4) = (0,1,0,0), $ then $(s_1, s_2,s_3,s_4) = (0,0,1,0), $ then $(s_1, s_2,s_3,s_4) = (0,0,0,1), $ you are set. $\endgroup$ – Will Jagy May 29 '13 at 4:50
  • $\begingroup$ 1),math.stackexchange.com/questions/275643/… $\endgroup$ – math110 May 29 '13 at 5:22
  • $\begingroup$ @math110: There may be some useful ideas there, but $H_n^2\ne H_n^{(2)}$, so this isn’t $A(2,1)$. $\endgroup$ – Brian M. Scott May 29 '13 at 5:24

Write down the function $$ g(z) = \sum_{n\geq1} \frac{z^n}{n}H_n^2, $$ so that $S=g(-1)$ and $g$ can be reduced to $$ zg'(z) = \sum_{n\geq1} z^n H_n^2 = h(z). $$

Now, using $H_n = H_{n-1} + \frac1n$ ($n\geq2$), we can get a closed form for $h(z)$: $$h(z) = z + \sum_{n\geq2}\frac{z^n}{n^2} + \sum_{n\geq 2}z^n H_{n-1}^2 + \sum_{n\geq 2} 2\frac{z^n}{n}H_{n-1}. $$ Now, the first and third sums Mathematica can evaluate itself in closed form (the third one evaluates to the function $p(z)$ below, the first one is $\text{Li}_2(z)-z$), and the middle sum is $z h(z)$.

Substituting this into the expression for $g(z)$, we get $$g(z) = \int \frac{\text{Li}_2(z) + p(z)}{z(1-z)}\,dz, $$ $$p(z) = -\frac{\pi^2}{3} + 2\log^2(1-z)-2\log(1-z)\log(z)+2\text{Li}_2((1-z)^{-1}) - 2\text{Li}_2(z). $$ Mathematica can also evaluate this integral, giving (up to a constant of integration) \begin{align} g(z) &= \frac{1}{3} \left(-2 \log(1-z^3+3 \log(1-z)^2 \log(-z)+\log(-1+z)^2 (\log(-1+z)+3 \log(-z) \right. \\ & \hspace{5mm} \left. -3 \log(z))+\pi ^2 (\log(-z)-2 \log(z))+\log(1-z) \left(\pi^2 - 3 \log(-1+z)^2 \right. \right.\\ & \hspace{5mm} \left.\left. +6 (\log(-1+z)-\log(-z)) \log(z)\right)-6 (\log(-1+z)-\log(z)) \left(\text{Li}_{2}\left(\frac{1}{1-z}\right)-\text{Li}_{2}(z)\right) \right.\\ & \hspace{10mm} \left. -3 \log(1-z) \text{Li}_{2}(z)+3 \text{Li}_{3}(z)\right). \end{align} The constant of integration is fixed by requiring $g(0)=0$.

Some care needs to be taken, because the function is multi-valued, when evaluating $g(-1)$. The answer is $$ \frac{1}{12}(\pi^2\log2-4(\log 2)^3-9\zeta(3)). $$


let $$y=\sum_{n=1}^{\infty}H^2_{n}x^n$$

then we have $$y=x+xy+\ln^2{(1-x)}+\int_{0}^{x}\dfrac{\ln{(1-t)}}{t}dt$$

so $$y=\dfrac{\ln^2{(1-x)}}{1-x}+\sum_{n=1}^{\infty}\left(1+\dfrac{1}{2^2}+\cdots+\dfrac{1}{n^2}\right)x^n$$

then you can use:Proving an alternating Euler sum: $\sum_{k=1}^{\infty} \frac{(-1)^{k+1} H_k}{k} = \frac{1}{2} \zeta(2) - \frac{1}{2} \log^2 2$


we have $$ \frac{\ln^2(1-x)}{1-x}=\sum_{n=1}^{\infty}\left(H_n^2-H_n^{(2)}\right)x^n$$

replace $x$ with $-x$, divide both sides by $x$ then integrate w.r.t $x$ from $0$ to $1$ , we get: \begin{align*} S_1&=\sum_{n=1}^{\infty}(-1)^n\left(H_n^2-H_n^{(2)}\right)\int_0^1x^{n-1}\ dx=\sum_{n=1}^{\infty}\left(H_n^2-H_n^{(2)}\right)\frac{(-1)^n}n=\underbrace{\int_0^1\frac{\ln^2(1+x)}{x(1+x)}\ dx}_{x=\frac{1-y}{y}}\\ &=\int_{1/2}^1 \frac{\ln^2x}{1-x}\ dx=\sum_{n=1}^{\infty}\int_{1/2}^1x^{n-1}\ln^2x\ dx=\sum_{n=1}^{\infty}\left(\frac{2}{n^3}-\frac{2}{2^n n^3}-\frac{2\ln2}{2^n n^2}-\frac{\ln^22}{2^n n}\right)\\ &=2\zeta(3)-2\operatorname{Li_3}\left(\frac12\right)-2\ln2\operatorname{Li_2}\left(\frac12\right)-\ln^32 \end{align*}

Now using the identity:

$$\displaystyle \int_0^1x^{n-1}\ln^2(1-x)\ dx=\frac1n\left(H_n^2+H_n^{(2)}\right)$$

multiply both sides by $(-1)^n$ then sum both sides w.r.t $n$ from $1$ to $\infty$, we get \begin{align*} S_2&=\sum_{n=1}^{\infty}\left(H_n^2+H_n^{(2)}\right)\frac{(-1)^n}{n}=\int_0^1\frac{\ln^2(1-x)}{x}\sum_{n=1}^{\infty}(-x)^n\ dx=\underbrace{-\int_0^1\frac{\ln^2(1-x)}{1+x}\ dx}_{x=1-y}\\ &=-\int_0^1\frac{\ln^2(x)}{2-x}=-\sum_{n=1}^{\infty}\frac1{2^n}\int_0^1 x^{n-1}\ln^2x\ dx=-2\sum_{n=1}^{\infty}\frac1{2^n n^3}=-2\operatorname{Li_3}\left(\frac12\right) \end{align*} we are now ready to calcualate our sum: \begin{align*} \frac{S_1+S_2}{2}=\sum\frac{(-1)^n H_n^2}{n}&=\zeta(3)-2\operatorname{Li_3}\left(\frac12\right)-\ln2\operatorname{Li_2}\left(\frac12\right)-\frac12\ln^32\\ &=\frac12\ln2\zeta(2)-\frac34\zeta(3)-\frac13\ln^32 \end{align*}

and as a bonus : \begin{align*} \frac{S_2-S_1}{2}=\sum\frac{(-1)^n H_n^{(2)}}{n}&=\ln2\operatorname{Li_2}\left(\frac12\right)-\zeta(3)+\frac12\ln^32\\ &=\frac12\ln2\zeta(2)-\zeta(3) \end{align*}

where the results of $\operatorname{Li_3}\left(\frac12\right)=\frac78\zeta(3)-\frac12\ln2\zeta(2)+\frac16\ln^32$ and $ \operatorname{Li_2}\left(\frac12\right)=\frac12\zeta(2)-\frac12\ln^22$ were used in the calculations.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.